Immunogenicity and safety of the first indigenously developed Indian tetravalent influenza vaccine (split virion) in healthy children (6 months to 17 years of age): a randomized, multicenter, phase III clinical trial - Sumantra Sarkar; Chandrakant Bokade; Kapil Garg; Ravi Kumar; Jayesh Sanmukhani; Ravindra Mittal (Taylor & Francis Group, 2021)
This phase III clinical trial was conducted to evaluate the immunogenicity and safety of the Tetravalent Influenza Vaccine (Split virion) I.P. (TetIV), containing two strains each of influenza A and B, developed indigenously in the country for the first time by M/s Cadila Healthcare Limited, India for use in the pediatric population (6 months −17 years of age), and compare it to that of a licensed seasonal Trivalent Influenza Vaccine (TriIV) of Sanofi Pasteur India Private Limited, containing two influenza A and one influenza B strains. Three hundred six subjects of either sex, 6 months to 17 years of age, were randomized in a 1:1 ratio to receive either TetIV or TriIV. Immunogenicity assessments (antibodies against A/H1N1, A/H3N2, B/Phuket, and B/Brisbane) were performed using the hemagglutination inhibition assay at baseline and 28 days after the last vaccination. TetIV was found to fulfill the criteria set by the United States Food and Drug Administration on the requirements of clinical data for licensure of seasonal inactivated influenza vaccines for the pediatric population. The seroconversion rates with TetIV were 94.6% for A/H1N1, 93.9% for A/H3N2, 91.2% for B/Brisbane, and 87.2% for B/Phuket strains. TetIV showed non-inferiority and superiority in immune response, as compared to TriIV, against the shared strains and an additional B strain, respectively. Both the vaccines were tolerated well by all the study participants, and an addition of the fourth strain in TetIV did not compromise the safety as compared to that of TriIV. The most common adverse event reported in both groups was fever.